Eficacia de la facoemulsificación vs la técnica Mininuc en el resultado de la agudeza visual en pacientes con catarata senil en el Hospital IV Víctor Lazarte Echegaray de EsSalud – La Libertad – 2020 - Fonseca Risco, Julio César (2020)
The present investigation project has as a problem: What is the efficacy of phacoemulsification vs the mininuc technique in the result of visual acuity in patients with senile cataract at Hospital IV Víctor Lazarte Echegaray de Essalud - La Libertad - 2020?; as general objective: To determine the efficacy of phacoemulsification with the mininuc technique in the result of visual acuity in patients with senile cataract at Hospital IV Víctor Lazarte Echegaray de Essalud - La Libertad - 2020; As a hypothesis it was proposed: The phacoemulsification technique is more effective in the result of visual acuity than the mininuc technique in patients with senile cataract at Hospital IV Víctor Lazarte Echegaray de Essalud - La Libertad 2020. The sample will consist of 148 patients with diagnosis of senile cataract over 60 years of age. Study with a quantitative, descriptive, retrospective, correlational, comparative, non-experimental approach. The instrument was the data collection sheet. The statistical analysis will be carried out with the statistical software SPSS Vss 26.00; using descriptive statistics and inferential statistics. For the elaboration and execution of the investigation project, the Declaration of Helsinki of the World Medical Association (WMA) will be considered.